2021
DOI: 10.1186/s13223-021-00528-3
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of promotional material for asthma-related products and therapies on Instagram

Abstract: Background Increasingly, social media is a source for information about health and disease self-management. We conducted a content analysis of promotional asthma-related posts on Instagram to understand whether promoted products and services are consistent with the recommendations found in the Global Initiative for Asthma (GINA) 2019 guidelines. Methods We collected every Instagram post incorporating a common, asthma-related hashtag between Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The promotional content posted by pharmaceutical companies in our study was 24%. In a study by Heineman et al [ 10 ] on asthma therapies, the researchers found that 42% of the information was promotional, and of that, only 32% was consistent with the Global Initiative for Asthma guidelines, leaving a significant amount of information lying around that was not supported by the Global Initiative for Asthma. This is a favorable finding because it is necessary that information about healthcare-related conditions is not driven by the promotional strategies of pharmaceutical companies, which might try to promote their own products using social media platforms, thereby modifying the decision-making capacities of the patients and preventing accurate information transmission to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promotional content posted by pharmaceutical companies in our study was 24%. In a study by Heineman et al [ 10 ] on asthma therapies, the researchers found that 42% of the information was promotional, and of that, only 32% was consistent with the Global Initiative for Asthma guidelines, leaving a significant amount of information lying around that was not supported by the Global Initiative for Asthma. This is a favorable finding because it is necessary that information about healthcare-related conditions is not driven by the promotional strategies of pharmaceutical companies, which might try to promote their own products using social media platforms, thereby modifying the decision-making capacities of the patients and preventing accurate information transmission to them.…”
Section: Discussionmentioning
confidence: 99%
“…YouTube has been a source for sharing information, not just about obesity but about several healthcare diseases like stroke [6][7][8][9], asthma [10,11], myocardial infarction [12], and breast cancer [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The full search was carried out within 1 day by both researchers due to daily fluctuations in the content available under the hashtag. This volume of posts was chosen to provide an overview of the content during these periods as per the methodology of previous content analysis literature on other topic‐specific hashtags (Heineman et al., 2021; Parker et al., 2021). These posts were compiled on Microsoft Excel.…”
Section: Methodsmentioning
confidence: 99%
“…Allows companies to get customers even companies only need to pay internet fees. F. Building Relationships Companies can build relationships with customers who have made transactions, it really helps companies to increase customer retention and companies can ask for reviews from every customer regarding the company's products, making it easier for companies to evaluate if there are errors or deficiencies and give thanks to customers [13].…”
Section: What Are the Benefits Of Promotion Using Social Mediamentioning
confidence: 99%